(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This study aims to think about the artistic creation process as a matrixial borderspace. Anchored in the methodological approach of bricolage, the creation of the performative dance Tú, él, nosostros tres, inspired by works by Mexicans artists Frida Kahlo, Arturo Estrada and Nahum B. Zenil, is analyzed. Thus, the creative process is understood as a space/womb modeled by interconnections and permeabilities, which generates the work of art, and capable of recreating the artist himself.